STUDENTS’ PERCEPTION OF ENGLISH MOVIE IN ENHANCING LISTENING SKILL LEARNING MOTIVATION: A DESCRIPTIVE QUANTITATIVE STUDY - Hilaria Janariani; Fariska Wulandari (LPPM STBA Pontianak, 2026)
This study explores students’ perceptions of using movies to enhance their motivation in learning listening. Motivation is essential in language learning, yet listening often poses challenges that reduce students’ interest. A descriptive quantitative method was employed, involving 30 second-semester students of the English for Business and Professional Communication program who had prior experience learning through movies. Data were collected using a questionnaire distributed via email and WhatsApp and analyzed using percentage scores. Results show that students hold positive perceptions of using movies in listening classes. Most respondents strongly agreed that movies are authentic (63%), useful (63%), and effective (57%) learning tools. They also believed movies make learning listening more interesting (70%) and enjoyable (70%), help reduce anxiety, and provide authentic language input, real-life context, and engaging content. Overall, students perceive movies as a motivating and effective medium for developing listening skills.